Hyperlipidemia is involved in apoptosis in rat submandibular glands. (September 2017) - Irie, Koichiro; Tomofuji, Takaaki; Ekuni, Daisuke; Azuma, Tetsuji; Yoneda, Toshiki; Shimazaki, Yoshihiro; Morita, Manabu
Highlights: Plasma level of oxLDL was higher in hyperlipidemic rats than in control rats. Structural changes in submandibular glands were found in hyperlipidemic rats. OxLDL may trigger off a reaction of apoptosis in the submandibular glands. Abstract: Objective: The aim of the present study was to investigate the effects of hyperlipidemia on histological changes and apoptosis in submandibular glands using apolipoprotein E (apoE)-deficient rats. Design: Histopathological findings related to induced apoptosis in the submandibular glands were compared between apoE-deficient rats (n = 6; male; age, 16 weeks) and the corresponding wild-type rats (n = 6). Results: ApoE-deficient rats showed significantly higher plasma levels of oxidized low-density lipoprotein (LDL), total cholesterol, very LDL and LDL, and lower plasma levels of high-density lipoprotein when compared to control rats ( P <  0.05). Lipid deposition in the submandibular gland was observed in apoE-deficient rat group and in none of the control group. Significant increases in vacuolization and apoptosis in acinar cells were observed in apoE-deficient rats, as compared to control rats ( P  < 0.05). The number of active caspase-3-positive cells was also higher in the apoE-deficient rat group when compared with the control group ( P  < 0.01). Conclusions: According to our results, hyperlipidemia induced apoptosis in apoE-deficient rat submandibular glands. Oxidized LDL generation in case of hyperlipidemia may trigger off a reaction of apoptotic acinar cells with vacuolization in the submandibular glands.